موارد المياه الجوفية في سهل عكار - علي محمد الأسعد; عباس عبد الرحمن عبد الرحمن; شريف بدر حايك (Tishreen University, 2019)
تشغل منطقة البحث الجزء الجنوبي من سهل عكار, التي تمتاز بأهمية اقتصادية كبيرة، لوفرة مصادرها المائية وخصوبة أراضيها الزراعية، واعتماد عدد كبير من سكانها على الإنتاج الزراعي. وقد تسبّبت ظروف التغذية والصرف الجديدة، واستثمارشبكات الري في سهل عكار منذ عام 2001, بتغيرات هيدروجيولوجية هامة كزيادة المساحات التي تتوضع فيها المياه الجوفية على عمق أقل من 3 م في المنطقة السهلية، من 15 كم2 في أيلول 1984 إلى 21 كم2 في أيلول 2002. بينما تزايدت الأعماق في المنطقة التلالية بحدود 7 م في أيلول 2002, بسبب استثمار الطبقة الحاملة للمياه الجوفية من قبل المزارعين ومؤسسة مياه الشرب في طرطوس. كما ساهمت الخصائص الهيدروديناميكية لجريانات المياه الجوفية في أراضي منطقة البحث بصرف كميات كبيرة نسبياً من المياه الجوفية في البحر وفي نهري الكبير الجنوبي والأبرش, وصلت إلى 17 مليون م3/ سنة. وتبين الموازنة المائية للمنطقة المدروسة، توفر مصادر مائية جوفية وسطحية جيدة, مما يستدعي وضع خطط لترشيد استثمارها بالشكل الأمثل.   The Research area covers the southern area of AKKAR plain, which is distinguished by its great importance caused by the abundance of water sources, and the fertility of its farming lands, and the fact that the vast majority of the inhabitants depend on farming. The discharge and recharge conditions, and the exploitation of the irrigation net in the AKKAR plain since 2001 caused important hydrogeological changes, as  the increasing of the area where groundwater exists, in less than 3m depth from 15 km2 in September 1984 to 21 km2 in September 2002, in the flat area. on the other hand, the groundwater depth in the hills area increased about 7m, because of the exploitation of the aquifer by the farmers and the Tartous water supply authority. Huge quantity of the groundwater flows into the sea, AL- Kabeer AL- Janoubi and the AL-Abrash Rivers, to reach 17 million m3 / year,, because of the hydrodynamic properties of the groundwater flow in the research area. Water balance of the studied area confirmed the existence of good resources for ground and surface water which requires the introduction of rational plans for the optimum investment in the future.